Pharmacokinetics and Pharmacodynamics of Key Components of a Standardized Centella asiatica Product in Cognitively Impaired Older Adults: A Phase 1, Double-Blind, Randomized Clinical Trial - Kirsten M. Wright; Melissa Bollen; Jason David; Alex B. Speers; Mikah S. Brandes; Nora E. Gray; Armando Alcázar Magaña; Christine McClure; Jan F. Stevens; Claudia S. Maier; Joseph F. Quinn; Amala Soumyanath (MDPI AG, 2022)
Centella asiatica is reputed in Eastern medicine to improve cognitive function in humans. Preclinical studies have demonstrated that aqueous extracts of C. asiatica improve cognition in mouse models of aging and Alzheimer's disease (AD) through the modulation of mitochondrial biogenesis and nuclear factor-erythroid-2-related factor 2 (Nrf2)-dependent antioxidant response genes. This randomized, double-blind, crossover Phase I trial explored the oral bioavailability and pharmacokinetics of key compounds from two doses (2 g and 4 g) of a standardized C. asiatica aqueous extract product (CAP), over 10 h, in four mildly demented older adults on cholinesterase inhibitor therapy. The analysis focused on triterpenes (TTs) and caffeoylquinic acids (CQAs), which are known to contribute to C. asiatica's neurological activity. The acute safety of CAP and the effects on NRF2 gene expression in peripheral blood mononuclear cells were evaluated. Single administration of 2 g or 4 g of CAP was safe and well-tolerated. The TT aglycones, asiatic acid and madecassic acid, were identified in plasma and urine, while the parent glycosides, asiaticoside and madecassoside, although abundant in CAP, were absent in plasma and had limited renal excretion. Similarly, mono- and di-CQAs showed delayed absorption and limited presence in plasma or urine, while the putative metabolites of these compounds showed detectable plasma pharmacokinetic profiles and urinary excretion. CAP elicited a temporal change in NRF2 gene expression, mirroring the TT aglycone's pharmacokinetic curve in a paradoxical dose-dependent manner. The oral bioavailability of active compounds or their metabolites, NRF2 target engagement, and the acute safety and tolerability of CAP support the validity of using CAP in future clinical studies.